EFFECT OF A SHORT PERIOD WHOLE BODY VIBRATION WITH 10 HZ ON BLOOD BIOMARKERS IN WISTAR RATS - Monteiro, Milena de Oliveira Bravo; Sá-Caputo, Danúbia da Cunha de; Moreira-Marconi, Eloá; Frederico, Éric Heleno Freire Ferreira; Sousa-Gonçalves, Cintia Renata de; Bernardo, Luciana Camargo; Guimarães, Carlos Alberto Sampaio; Bernardo-Filho, Mario (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Exposure to whole body vibration exercises (WBVE), besides some biological effects, causes alterations in the concentration of some blood biomarkers. The aim of this study is to evaluate the action of vibration (10 Hz) of WBVE on the concentration of blood biomarkers in Wistar rats. Materials and Methods: Wistar rats were divided in 2 groups. The experimental group (EG) was subjected to vibrations of 10Hz (one min per day, one week, total time of seven min), while the control group (CG) has not experienced vibration. Samples of whole blood were drawn for biochemical analysis of the concentration of total cholesterol, triglycerides, HDL, LDL, VLDL, glucose, CPK, albumin, alkaline phosphates, TGP, TGO, γGT, lipase, amylase, urea and creatinine. Results: White blood cell count and a platelet-hemogram were also performed. Significant (p<0.05) increase in TGP, TGO and white blood cells and decrease in LDL concentration was found after exposure of 10Hz mechanical vibration. Conclusion: Although these findings were obtained with rats, they might contribute to try to understand better these mechanisms that occur following exposure to a frequency of 10Hz.